(untitled) (Journal of the College of Basic Education, 2022)
Abstract List of Abbreviations: EFL English Foreign Language GE General English TPS Think Pair Share 1-Introduction 1.1 Problem of the Study and its Significance: General English ( henceforth GE)as a subject matter represents practical real life needs. It covers the basic language skills which are speaking, listening, reading and writing. From the researchers’ experience in EFL teaching at college level, they notice that many students have different difficulties and problems in mastering these skills. They make different mistakes in English grammar, pronunciation, orthography and vocabulary usage and they are not engaged actively in the learning process. McLaughlin et al. (1983:144) state that to develop any complex or difficult skill, teachers must employ a set of good automatic procedures. Ledlow (2001: online)believes that there are problems with the way that questions are usually posed within a lecture. One of these problems is that when a question is posed to the class as a whole, usually some students, and sometimes no student, volunteer to answer the question. Another problem is that usually after asking a question, the instructor waits less than one second before calling on a student. Meanwhile the first student is called to answer, other students stop processing their answers.